Predicting Stock Returns by Using Financial Ratios - Rezvan Hejazi; Mahboobe Fatemi (مطالعات تجربی حسابداری مالی, 2005)
Accounting information in order to be effective in decision making, should be relevance and reliable. On the other hand, the usefulness of the financial statements information depend on explanatory and  predictive power of companies value and the latter is directly affected by current and future returns .Therefore , this study aims at investigating predicting stock returns using financial  ratios. The four ratios driven of research literature include earning to price,  book to price, sales to price and dividend to price   ratios. The statistical population taking part in this study includes the Accepted companies in Tehran securities exchange and a sample of 72 companies in different industries during 1378-1383. The results show that in relating to variables investigated, there is the greatest explanatory power between book to price ratio and stock returns and Earning to price ratio has not meaningful relation with the future stock returns. Keywords: Stock return, earning to price ratio, book to price ratio, sales to price ratio, dividend to price ratio.